No evidence of a correlation between lumbar spinal subtypes and intervertebral disc degeneration among asymptomatic middle-aged and aged patients - Wang, Ben (Exp Ther Med, 2020)
The aim of the present study was to identify whether lumbar spinal subtypes (LSS) were associated with lumbar disc degeneration (LDD) among asymptomatic middle-aged and aged subjects. A cohort of 158 asymptomatic Chinese adults aged >40 years was recruited and 97 volunteers that met the inclusion criteria with complete information available were selected for inclusion. According to spinal morphology, volunteers were divided into four subtypes based on the classification of Roussouly. After baseline information was collected and spinopelvic parameters were measured, the data were compared among the four groups. According to the Pfirrmann classification, the degree of LDD was evaluated at each level on the MRI. For grades I-V, LDD at each level was effectively compared. Each of the four LSS from I to IV according to Roussouly classification from types I to IV were comprised of 25 (25.8%), 19 (19.6%), 38 (39.2%) and 15 (15.5%) of volunteers, respectively. Lumbar lordosis, sacral slope and pelvic incidence were significantly different among the four sub-types (P<0.001 for each), but no difference in pelvic tilt was observed (P=0.21). From types I to IV LSS, the proportion of disc degeneration was found to be 44, 52, 50 and 48%, respectively, which exhibited no statistically significant difference among LSS. No correlation between LSS and intervertebral disc degeneration was obtained among the asymptomatic middle-aged and aged subjects. The present study provides a reference for spinal surgery and indicated that additional risk factors should be assessed in the asymptomatic population of this age group, particularly in terms of differentially expressed genes.